Gαs Protein Expression Is an Independent Predictor of Recurrence in Prostate Cancer. (31st March 2014) - Wang, Lijuan; Jin, Guihua; He, Chenchen; Guo, Xijing; Zhou, Xia; Li, Meng; Ying, Xia; Wang, Le; Wu, Huili; Zhu, Qing
Abstract : Background . T393C polymorphism in the gene GNAS1, which encodes the G-protein alpha s subunit (G α s) of heterotrimeric G protein, is significantly associated with the clinical outcome of patients suffering from several cancers. However, studies on the role and protein expression of G α s subunit in prostate cancer were still unavailable. Methods . The immunohistochemical staining was used to assess G α s expression through tissue microarray procedure of 56 metastatic PCas, 291 localized PCas, and 67 benign hyperplasia (BPH). G α s expression was semiquantitatively scored and evaluated the correlation with pathologic parameters and biochemical recurrence of prostate-specific antigen (PSA). Results . G α s expression was localized in nuclear and cytoplasm in prostate cancer cells and downregulated in metastatic PCa compared to localized PCa and BPH ( P < 0.001 ) . G α s was inversely associated with PSA level and Gleason scores; patients with low expression of G α s had adverse clincopathological features. In multivariable Cox regression analysis, high G α s expression and Gleason scores were independent predictors of both PSA progression-free and overall survival. Conclusions . G α s down-expression is associated with adverse pathologic features and clinical PSA biochemical recurrence of prostate cancer. G α s is an independent predictor to help determine the risk of PSA progression and death.